2023
DOI: 10.3390/jcm12062107
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Visual Recovery with Time in Epiretinal Membrane Surgery: A Predictive Analysis Based on Retinal Layer OCT Thickness Changes

Abstract: Purpose: To correlate postoperative optical coherence tomography (OCT) thickness changes of each retinal layer with different patterns of visual recovery after idiopathic epiretinal membrane (ERM) surgery in a cohort of patients showing no known risk factors for poor visual recovery at preoperative imaging. Methods: Best corrected visual acuity (BCVA) and OCT images were acquired preoperatively and 1 month, 3 months and 6 months postoperatively. Patients were divided into four groups according to postoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Optical coherence tomography (OCT) is a well-known technique that allows us to quantitatively map and measure distinctive layers of the retina. In the study of Romano et al [3], the thicknesses of the central macula, inner layer, retinal nerve fiber layer, ganglion cell layer, inner plexiform layer, inner nuclear layer, outer plexiform layer, and outer nuclear layer were measured by OCT, and the best-corrected visual acuity (BCVA) was recorded in the patients with an idiopathic epiretinal membrane before the operation, as well as 1, 3, and 6 months after the operation. The patients were divided into four groups with different levels of visual recovery, according to the postoperative BCVA improvement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optical coherence tomography (OCT) is a well-known technique that allows us to quantitatively map and measure distinctive layers of the retina. In the study of Romano et al [3], the thicknesses of the central macula, inner layer, retinal nerve fiber layer, ganglion cell layer, inner plexiform layer, inner nuclear layer, outer plexiform layer, and outer nuclear layer were measured by OCT, and the best-corrected visual acuity (BCVA) was recorded in the patients with an idiopathic epiretinal membrane before the operation, as well as 1, 3, and 6 months after the operation. The patients were divided into four groups with different levels of visual recovery, according to the postoperative BCVA improvement.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between the thicknesses of the retinal layers and the four visual recovery patterns were analyzed. It was concluded that different patterns of BCVA recovery were associated with the different thickness changes in different retinal layers [3]. In the review about the relationship between choroidal thickness (CT) measured by OCT and primary open-angle glaucoma (OAG), Verticchio Vercellin et al investigated the feasibility of using CT as a new biomarker of OAG [4].…”
Section: Introductionmentioning
confidence: 99%